دوہزار اٹھارہ عیسوی میں رمضان المبارک میں پاکستانی ٹیلی ویژن پر نشر کیے جانے والے اسلامی پروگراموں کا تنقیدی جائزہ: A Critical Analysis of Islamic programs Aired on Pakistani Television in Ramadan of year 2018 - Alia Jabeen,; Dr Shah Mohyuddin Hashmi, (MEI, 2023)
The purpose of this research is to study the topics and the authenticity of the content discussed in Islamic programs aired on Pakistani television in the Holy month of Ramadan in the Islamic year 1439. For this purpose, five popular Pakistani TV channels were chosen for study, i.e., GEO, ARY, PTV, Dunya and Samaa. From amongst these five channels, five programs each from the month of Ramadan were chosen and were analysed based on the Quranic, Hadith and historical references cited by the scholars who appeared as guests on the programs. The analysis mainly covers a critical study of the authenticity of the Ayaat, Ahadith and historical events narrated. This study also attempts to discern how successful these Ramadan transmissions are in conveying authentic information to their viewers.